Perspectives on athlete-centered coaching - Pill, Shane (Routledge, Taylor & Francis Group, 2018)
"Underpinned by a philosophy of empowerment, athlete-centred approaches to coaching are defined by a style that promotes learning through ownership, responsibility, initiative and awareness. Perspectives on Athlete-Centred Coaching offers an in-depth theoretical examination of player-focused coaching models, and provides professional guidance for practising coaches. Written by a cast of world-leading scholars and practitioners, and offering a breadth of approaches to, and critiques of, the application of athlete-centred coaching, the book covers topics including: - athlete-centered coaching and holistic development - coaching tactical creativity - athlete-centred coaching in disability sport - team culture and athlete-centred coaching - developing thinking players through Game Sense coaching - supporting athlete wellbeing - athlete-centred coaching and teaching games for understanding - athlete-centred coaching in masters sport Based on the latest research and offering the most comprehensive enquiry into this central area of coaching theory, Perspectives on Athlete-Centred Coaching is important reading for any students and lecturers of sports coaching or physical education, and practising coaches across any sport"-- Provided by publisher.